2020
DOI: 10.24036/ld.v14i2.108643
|View full text |Cite
|
Sign up to set email alerts
|

Interlanguage Analysis on Indonesian EFL Learners’ Compositions

Abstract: This study aims at investigating the interlanguage production by Indonesian EFL students in their English compositions. Interlanguage describes the language produced by second or foreign language learners when learning the target language. Forty college students majoring in English for tourism industry were the subjects in this study. In collecting the data, the students were asked to write a recount text with a topic "an experience of visiting a hotel” through a guided writing exercise. The framework of error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The participants also conduct error in using English words with similar meanings. The problems experienced with plural formation are revealed by various studies (Aini et al, 2020;Aziez, 2016;Burhansyah, 2019;Gayo & Widodo, 2018;Puspita, 2019;Suwastini et al, 2020;Tiarina, 2017). This present study also revealed grammatical characteristic produced by the participants namely assigning different lexical meaning.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The participants also conduct error in using English words with similar meanings. The problems experienced with plural formation are revealed by various studies (Aini et al, 2020;Aziez, 2016;Burhansyah, 2019;Gayo & Widodo, 2018;Puspita, 2019;Suwastini et al, 2020;Tiarina, 2017). This present study also revealed grammatical characteristic produced by the participants namely assigning different lexical meaning.…”
Section: Discussionsupporting
confidence: 70%
“…Overgeneralisation is a basic learning technique involving the learner's language, according to (Fauziati & Nugroho, 2019). The overgeneralisation of BE by Indonesians has been recorded by numerous studies (Aziez, 2016;Burhansyah, 2019;Fauziati, 2011Fauziati, , 2017Fauziati & Maftuhin, 2016;Kusumawardani & Adnyani, 2020;Pratiwi et al, 2020;Suwastini et al, 2020). Another findings also revealed the omission of the copula BE (i.e am, is, are).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It might be difficult to learn English as a second language due to the dissimilar nature of the target language and the student's mother tongue (Maheswari et al, 2020;Manik & Suwastini, 2020). This problem is typically more severe when the individual qualities of each student are considered (Uzair-ul-Hassan et al, 2019).…”
Section: Jeltlmentioning
confidence: 99%